Coase Lecture – The Glass Ceiling. (2nd March 2018) - Bertrand, Marianne
Abstract : Despite decades of progress, women remain underrepresented in the upper part of the earnings distribution. We review the recent research trying to explain this phenomenon. After briefly revisiting gender differences in education, we turn our attention to a body of work that has argued that gender differences in psychological attributes are holding back women's earnings. We then review another active area of research focused on the challenges that women may face when trying to juggle competing demands on their time in the workplace and the home, particularly when the home includes children. We discuss recent work documenting women's greater demand for flexibility in the workplace, as well as work measuring the labour market penalties associated with such demand for flexibility, particularly in the higher paying occupations in the economy. We highlight possible countervailing forces (both at work and at home) that may explain why these work–family considerations may remain highly relevant to today's glass ceiling despite reduced time spent in non‐market work and a trend towards a more equal division of non‐market work between men and women. Finally, we discuss the role that public policy and human resource practices may play in adding more cracks to the glass ceiling.